(untitled) (Third Sector Social Economic Review, 2024)
Despite the recent intense interest in the literature on the relationship between renewable energy and CO2 emissions, the impact of GDP, renewable energy and income inequality on consumption-based carbon dioxide (CO2) emissions has not been sufficiently investigated both theoretically and empirically. This study investigates the effects of GDP, renewable energy and income inequality on consumption-based CO2 emissions between 1990 and 2020 for Brazil, one of the world’s 10 largest economies, which has made a name for itself with its initiatives on renewable energy and carbon dioxide emissions. Thus, the study aims to reach effective policy strategies by revealing empirical evidence. SWIID database was used for the Gini index, which is an indicator of income inequality, while the World Bank database was used for other indicators. Multivariate regression analysis, PP and ADF unit root analyses, Johansen cointegration analysis and FMOLS estimation methods were used in this study. The empirical findings demonstrate both the long-term effect between variables and indicate that all independent variables influance the dependent variable CO2 emission between 1990-2020 for Brazil. In the concluding part of the paper, these findings are discussed in a broad perspective and some recommendations are given to Brazilian government and policy makers.